Biopolymer-Modified Carbon Paste Electrode for the Electrochemical Detection of Pb(II) in Water - Ousama Ifguis; Abdelaziz Moutcine; Charaf Laghlimi; Younes Ziat; Rachid Bouhdadi; Abdelilah Chtaini; Amine Moubarik; Mohamed Mbarki (Journal of Analytical Methods in Chemistry)
During the present study, biopolymer lignin was extracted, in particular, from sugar beet pulp (molasses) from the Tadla region (224 km from Marrakech, Morocco). The lignin was characterized by infrared spectroscopy (FTIR) and thermogravimetric TG/DTA analysis and then used as a modifier to enhance the electroanalytical detection of heavy metal ion traces. The performance of the lignin/CPE sensor to detect lead (II) was studied by cyclic voltammetry (CV) and square-wave voltammetry in 0.3 mol L−1 NaCl. With optimized experimental parameters, the lignin/CPE sensor developed has a minimum detection limit of 2.252.10−11 M for Pb (II). The proposed working electrode has been successfully applied for the coanalysis of Pb (II) in tap water with good results.